PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI DI BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN KARAWANG - Ahmad Yani (BUANA ILMU, 2018)
ABSTRACT The purpose of this study to obtain empirical evidence and to find clarity of phenomena and conclusions about the influence of career development and job motivation to job satisfaction and its impact to the performance of employee at Badan Pendapatan Daerah (Bapenda) Kabupaten Karawang. This research is expected to contribute to the development of management science especially as a contribution of scientific literature in human resources management, as reference material in scientific writing, as information material, both for leaders and colleagues in Badan Pendapatan Daerah Kabupaten Karawang in the implementation of performance-based management, As a material consideration and input in making decisions and determine the direction of policy. The research is done by using quantitative method with descriptive and verification method, that is collecting, presenting, analyzing and doing hypothesis testing, and making conclusion and suggestion. Based on the results of the research analysis, the following conclusions are obtained: the correlation of career development with work motivation has significant correlation, the influence of career development that directly affects employee job satisfaction, the influence of work motivation that directly affects employee job satisfaction, the influence of career development that directly affect the performance of employees, the influence of work motivation that directly affect the employee performance, the influence employee job satisfaction on employee performance, simultaneously career development and work motivation significantly influence employee job satisfaction, simultaneously career development and work motivation significantly influence job satisfaction which impact on employee performance improvement. Keywords: career development, work motivation, job satisfaction, employee performance